Giant pyogenic granuloma gravidarum of the hand - Khan, Ed Simor; Sharifudin, Mohd Ariff; Eshagroni, Ahmed; Mohamed Haflah, Nor Hazla; Abdullah, Shalimar; Sapuan, Jamari (Faculty of Medicine, International Islamic University Malaysia, 2014)
We describe a case of a giant pyogenic granuloma affecting the left index finger of a 23-year-old pregnant lady requiring surgical excision. Pyogenic granuloma gravidarum is a benign hyperplastic lesion that commonly presents on oral mucosa, typically the gums, in approximately 5% of pregnant women. Skin lesions over the fingers are an unusual site during pregnancy with only a few cases reported in the literature. The lesion was excised and a diagnosis of lobular capillary haemangioma was made based on histopathological evaluation. We delayed surgery until after parturition since recurrence is likely to be lower due to lower levels of circulating oestrogen and progesterone. The prognosis is usually excellent following resection. However, recurrences have been reported regardless of the treatment method.